Rare Columnar Cell Variant Papillary Thyroid Carcinoma with Metastasis to Pancreas and Lungs at Initial Presentation: A Case Report and Review of Literature - Gjeluci, Albert; Clark, Joseph; Jawahar, Anugayathri (Journal of Gastrointestinal and Abdominal Radiology, 2022)
Papillary thyroid cancer (PTC) is the most common endocrine malignancy, accounting for 85% of differentiated thyroid cancers. A small percentage of PTC variants are considered more aggressive, such as the tall cell variant associated with the V600E mutation in the BRAF gene and the rarer columnar variant, which is described in only 0.2% of cases and has a poor prognosis. Although locoregional metastases to neck lymph nodes are common, distant metastases of PTC are rare at presentation with only 5 to 7% reported in the literature. We present a very rare case of columnar cell variant PTC with synchronous metastasis to the lungs and indolent focus in the pancreas at initial diagnosis, which has never been reported in the literature. Our patient presented with non-radioactive iodine (RAI) responsive PTC with diffuse metastases to the lungs and one synchronous focal metastatic lesion in the pancreas. After multidisciplinary discussions, pancreatectomy/metastasectomy was deferred due to the disseminated PTC with multiple metastases to the lungs, lack of pancreas-related symptoms in the patient, and inherent complication risks. The patient was treated with systemic therapy using a tyrosine kinase inhibitor (lenvatinib), which is the standard of care for non-RAI responsive PTC and showed a complete radiologic resolution of the pancreatic lesion, however, with partial yet nonprogressive metastatic disease in the lungs.
Keywords: papillary thyroid cancer; columnar cell variant; pancreatic thyroid metastasis; PTC metastases